Pemanfaatan Alat Pengering Tenaga Surya Hybrid untuk Mengoptimalkan Produksi Simplisia Jahe di Desa Kayumas, Situbondo - Sulistyaningsih; Elieser Tarigan; Hazrul Iswadi; Elsye Tandelilin; Ani Listriyana; Yasmini Suryaningsih (JDISTIRA - Jurnal Pengabdian Inovasi dan Teknologi Kepada Masyarakat, 2023)
The aimed of this KOSABANGSA service activity is to apply solar power technology as a dryer to optimize the production of ginger simplicia and empower village communities to add value to ginger products through the Kayumas Village BUMDes. The location and time for carrying out this service is in Kayumas Village, Situbondo Regency from August-December 2023. The method used in this activity is training on controlling ginger plant diseases, especially Fusarium sp., handing over drying equipment along with a demonstration plot on the use of the equipment, then providing training on product packaging and create an official Instagram account and optimize it. Based on the results of the implementation of this service, it is to provide solutions to partners' problems in terms of production by providing training on controlling diseases in ginger and providing drying tools and socializing the use of tools so that ginger simplicia can be produced. Apart from that, the solution to answer the problem of marketing derivative products from ginger is with product packaging training and Instagram optimization training where the output is an official Instagram account which is optimized as a means of promoting ginger products and Kayumas ginger simplicia.